Transformasi Pendidikan PAUD dan Kesetaraan: Akselerasi Peningkatan dan Pendanaan - Dina Amelinda; Masduki Asbari; Hadisah (Journal of Information Systems and Management (JISMA), 2023)
Improvement and Funding is a form of educational service for intelligent and talented children which is provided with educational facilities in special groups with various models, the aim is to improve the quality of education in Indonesia. The government launched the ARKAS system with the aim of improving the management of BOS funds in educational units, including planning and reporting on the use of BOS funds. This research uses a qualitative descriptive research method. This approach is expected to produce in-depth descriptions of speech, writing, and behavior that can be observed from an individual, group, community, and organizational unit of analysis.